Maintaining The Teacher’s Performance of Saint Peter Primary School Kelapa Gading Teachers During Home Online Learning Amidst Covid 19 Pandemic - Yovita Della Herpriyanti; Bintang R Simbolon (Jurnal Syntax Transformation, 2021)
This qualitative research which has purpose to analyze how to maintain teacher’s performance during home online learning is using descriptive analysis method. Saint Peter Primary School has been using Microsoft 365 and Zoom application in all process of teaching learning and interaction between colleagues and all students during the pandemic time. The use of digital application features have been formed the primary basis of school administration which is conducted individually by teacher of Saint Peter Primary School and was monitored by the school principal. This research was conducted by processing the qualitative data obtained from in-depth interview towards informant of school staff and teachers of Saint Peter Primary School. The data collection was conducted through observation, in-depth interview towards informant and so was documentation. The subjects of this research are the school principal and also the teachers. In this qualitative research it is known that teacher’s performance appear in preparing, implementing and assessing the teaching learning with the use of digital applications during the online learning in pandemic time. Despite the all the weakness circumstances of home online learning, it is known that the quality of education is obviously adequate.